RANS/LES and LBM/VLES aero-acoustic analysis of weapon bays at transonic Mach number - Bacci, David; Saddington, Alistair J.; Ben-Gida, Hadar (American Institute of Aeronautics and Astronautics (AIAA), 2025)
Numerical aero-acoustic analysis was conducted on a weapon bay of a generic aircraft model using two conceptually different solvers, one based on the Navier-Stokes equations, the other based on the lattice-Boltzmann approach. The bay model was installed on a representative combat aircraft, incorporating doors and a store. The effect of angle of attack and store position on the aero-acoustic response within the weapon bay was analysed at a transonic Mach number of 0.90. It was found that both numerical approaches are capable of predicting, with good accuracy, the weapon bay’s acoustic spectrum (±10 dB) and store forces and moments (±10%),as compared to experimental data.